الميزة التنافسية للموقع الجغرافي وتنويع مصادر الدخل في الاقتصاد الليبي: The competitive advantage of geographical location and diversification of income sources in the Libyan economy - صابر المهدي الوحش, (Journal of North African Economies, 2025)
The research aimed to study the competitiveness of Libya’s geographical location, to identify its possible role in diversifying sources of income. The research relied on descriptive analysis through four axes: the first is concerned with competitiveness, the second is concerned with economic diversification and its indicators, and the third is concerned with indicators of African countries landlocked on the southern borders of Libya. The fourth presents the possible role of geographical location in diversifying sources of income in the Libyan economy, and a set of results were reached, the most important of which are: that Libya’s geographical location gives it a competitive advantage that enables it to diversify its sources of income; By establishing and activating free economic zones on its northern coast and southern borders, however, the achievement of these desired goals by these areas is weak as a result of the weak infrastructure represented by the dilapidated road network, the undeveloped banking system, and the weak communications network. Therefore, to activate the contribution of the geographical location in diversifying the sources of income in Libyan Economy The research recommended developing infrastructure projects and accelerating the establishment of free zones.